Upaya Menumbuhkan Minat Menabung Anak Usia Dini melalui Media Celengan Kreatif di Paud Nurul Islam Desa Jelutih Kecamatan Batin XXIV - Anita Juniyarni; Anjani Aprisia; Indah Rahmatul Zahra; Osa Pania Noprinda; Amiruddin Amiruddin; Maryam Maryam; Alfazri Rahmadani; Zila Wati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Instilling saving habits from an early age is an essential component of character education, particularly in fostering discipline, responsibility, and independence. Initial observations at PAUD Nurul Islam, Jelutih Village indicate that early childhood saving interest remains relatively low due to limited engaging learning media and the absence of structured habituation. This Community Service Program (KKN) aims to foster early childhood saving interest through creative piggy bank media aligned with children’s developmental characteristics. The implementation method comprised planning, execution, and evaluation stages. During execution, children were introduced to saving concepts through simple storytelling and interactive dialogue, followed by hands-on creation of creative piggy banks using simple, child-friendly materials. These piggy banks were then used to habituate saving behavior. The results demonstrate increased enthusiasm and saving interest among children, reflected in their willingness to set aside money and heightened responsibility toward their piggy banks. Therefore, creative piggy bank media serve as an effective alternative learning tool for fostering saving interest and positive character development among early childhood learners at PAUD Nurul Islam, Jelutih Village.